Regular measurement: A new method of biophysical experiment - Kolombet, V. A. (Biofizika, 2006)
A system of quantized relations between the value of the quantity being measured and the width of its experimental scattering was experimentally found in the results of measurements of rates of various processes. For determining D, the square of the ratio of the root-mean-square deviation to the mean value of the quantity being measured, particularly long series of stereotypic measurements under stable conditions, so-called regular measurements, are carried out. Regular changes in biochemical, chemical, and physical quantities show that the D value is related by a simple rational expression to the universal dimensionless constant D0 whose numerical value was measured with required accuracy. The simplicity of the ratios of D and D0 may result from the fact that, during regular measurements, the quantum behavior of the system macrodevice-object can be revealed.